Cancer Stem Cells in Drug Resistance and Drug Screening: Can We Exploit the Cancer Stem Cell Paradigm in Search for New Antitumor Agents? - Sabisz, Michal; Skladanowski, Andrzej (IntechOpen, 2011)
None